Specification for electromechanical components for electronic equipment: basic testing procedures and measuring methods. Impacttests (free components), static load tests (fixed components), endurance tests and overload tests. Tests 7b and 10a Part 5 Supplement No. 1, (27th February 1981) - British Standards Institution
No abstract available